2022
DOI: 10.1111/hdi.13006
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of predialysis hyperkalemia and associated characteristics among hemodialysis patients: The RE‐UTILIZE study

Abstract: Introduction: Hyperkalemia (HK), defined as serum potassium (K + ) >5.0 mEq/L, is an independent predictor of mortality in patients on maintenance hemodialysis (HD). This study investigated the annual prevalence of HK and examined patient characteristics potentially associated with a higher annual HK prevalence. Methods: This retrospective observational cohort study used Dialysis Outcomes and Practice Patterns Study (DOPPS) survey data from US patients undergoing in-center HD thrice weekly from 2018 to 2019. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In this study, the incidence of hyperkalemia was 39.65% in patients with hemodialysis. It was consistent with previous studies [ 6 , 25 ]. This study firstly developed a model for hyperkalemia prediction in patients with hemodialysis.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the incidence of hyperkalemia was 39.65% in patients with hemodialysis. It was consistent with previous studies [ 6 , 25 ]. This study firstly developed a model for hyperkalemia prediction in patients with hemodialysis.…”
Section: Discussionsupporting
confidence: 94%
“…A prospective study in France showed that 73.8% of patients on HD had predialysis hyperkalaemia (sK > 5.1 mmol/L) over 2 years [ 11 ]. In a retrospective observational cohort of patients on HD in the United States (US), 74% experienced predialysis hyperkalaemia (sK > 5.0 mEq/L) within 1 year, 52% within 3 months, and 38% within 1 month [ 8 ]. Another US database study showed that the prevalence of sK ≥ 5.5 mEq/L the day after a LIDI was 2.0–2.4 times higher than that the day after a SIDI [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalaemia, defined as elevated serum potassium (sK) levels, is a common complication among patients with ESRD, partly due to their diminished ability for renal potassium excretion [ 1 , 7 ]. Despite the removal of excess sK with HD treatment, 38–74% of patients with ESRD continued to have persistent hyperkalaemia during HD intervals [ 8 11 ]. Hyperkalaemia has been associated with adverse clinical outcomes, including significant arrhythmia, hospitalization, and all-cause mortality [ 10 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%